2013
DOI: 10.1074/mcp.m112.020115
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics with siRNA Screening Identifies Novel Mechanisms of Trastuzumab Resistance in HER2 Amplified Breast Cancers

Abstract: HER2 is a receptor tyrosine kinase that is overexpressed in 20% to 30% of human breast cancers and which affects patient prognosis and survival. Treatment of HER2-positive breast cancer with the monoclonal antibody trastuzumab (Herceptin) has improved patient survival, but the development of trastuzumab resistance is a major medical problem. Many of the known mechanisms of trastuzumab resistance cause changes in protein phosphorylation patterns, and therefore quantitative proteomics was used to examine phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 67 publications
(74 reference statements)
4
47
0
Order By: Relevance
“…Several studies highlight the importance of the analysis of protein phosphorylation in elucidating the radio- and chemoresistance mechanisms and identifying promising drug combinations [6,30,31,96103]. For example, a phosphoproteome array in HNSCC cells treated with cetuximab showed activation of the c-Jun N-terminal kinase (JNK) pathway which attenuated the efficacy of cetuximab itself [30].…”
Section: Proteome and Phosphoproteome Analysis In Revealing Bypass Anmentioning
confidence: 99%
“…Several studies highlight the importance of the analysis of protein phosphorylation in elucidating the radio- and chemoresistance mechanisms and identifying promising drug combinations [6,30,31,96103]. For example, a phosphoproteome array in HNSCC cells treated with cetuximab showed activation of the c-Jun N-terminal kinase (JNK) pathway which attenuated the efficacy of cetuximab itself [30].…”
Section: Proteome and Phosphoproteome Analysis In Revealing Bypass Anmentioning
confidence: 99%
“…EFS and other proteins involved in SRC kinase signaling (CDCP1/Trask and Paxillin) were showed to have increased expression in a study of breast cancer using trastuzumab (Herceptin)-resistant versus -sensitive BT474 cell line derivatives [93]. Importantly, EFS knockdown with siRNA restored trastuzumab sensitivity [93].…”
Section: Implication Of Efs and Cass4 In Other Disordersmentioning
confidence: 99%
“…Importantly, EFS knockdown with siRNA restored trastuzumab sensitivity [93]. Reflecting the importance of post-translational modification of CAS proteins, in a study of cell lines and tumor tissue in malignant melanoma, EFS phosphorylation and activity significantly decreased (p<0.05) in response to vemurafenib treatment in BRAF wild-type melanoma tumors compared to tumors with a BRAF V600E mutation with additional resistance to vemurfenib [94].…”
Section: Implication Of Efs and Cass4 In Other Disordersmentioning
confidence: 99%
“…Another powerful example of the role of CDCP1 in mediating poor response to therapy involves breast cancer resistance to the HER2 targeted therapeutic antibody trastuzumab. A quantitative proteomics screen comparing the phospho-tyrosine (p-Y) content of trastuzumab-sensitive and -resistant breast cancer cell lines identified 12 fold higher levels of p-Y-CDCP1 in resistant cells [20]. Confirming the role of CDCP1 in resistance in this model, siRNA mediated silencing of CDCP1 restored cell line responsiveness in vitro to trastuzumab [20].…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative proteomics screen comparing the phospho-tyrosine (p-Y) content of trastuzumab-sensitive and -resistant breast cancer cell lines identified 12 fold higher levels of p-Y-CDCP1 in resistant cells [20]. Confirming the role of CDCP1 in resistance in this model, siRNA mediated silencing of CDCP1 restored cell line responsiveness in vitro to trastuzumab [20]. Further supporting that CDCP1 is important in breast cancer resistance to trastuzumab, a more recent study demonstrated that CDCP1 and HER2 are co-overexpressed in 12% of primary and 30% of metastatic breast tumors, and that co-expression correlates with poorest disease free and overall survival [21].…”
Section: Introductionmentioning
confidence: 99%